Spectral World Musics: Proceedings of the Istanbul Spectral Music Conference 2003 - Reigle, Robert; Whitehead, Paul (Istanbul Pan Yayincilik, 2008)
This collection is an outcome of the Spectral Musics Conference held at Istanbul Technical University, 18-23 November 2003, organized by Michael Ellison, Robert Reigle, and Pieter Snapper.Written from a variety of perspectives by experts in such fields as composition, ethnomusicology, historical musicology, performance, and improvisation, this collection of papers sheds new light on the history of timbre and spectral thinking. As Robert Reigle explains in his important introduction, "Some musics around the world clearly foreground timbre, and these may unambiguously be called 'spectral musics'." The Istanbul Spectral Music Conference, at which these papers were presented, therefore redefined "spectral music" to encompass any music foregrounding timbre as an important element of structure or musical language.
Keywords: Folk music; Spectral music; Artistic research